2013
DOI: 10.9790/0837-1310107
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Fiscal Decentralization on Local Economic Development in East Java

Abstract: This research aims at investigating and analyzing the impact of implementation of fiscaldecentralization on local economic development in East Java.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…They found that nonmetropolitan counties reported greater fiscal stress due to revenue requirements of decentralization. This finding is particularly important since counties play an important role in the American federal system in promoting local economic development and growth Jumadi et al, (2013), analyzed the impact of implementation of fiscal decentralization on local economic development in East Java. This study uses panel data across districts and cities in East Java Province, which consists of 29 districts and 9 cities in 2007-2010.…”
Section: Research Hypothesesmentioning
confidence: 99%
“…They found that nonmetropolitan counties reported greater fiscal stress due to revenue requirements of decentralization. This finding is particularly important since counties play an important role in the American federal system in promoting local economic development and growth Jumadi et al, (2013), analyzed the impact of implementation of fiscal decentralization on local economic development in East Java. This study uses panel data across districts and cities in East Java Province, which consists of 29 districts and 9 cities in 2007-2010.…”
Section: Research Hypothesesmentioning
confidence: 99%
“…The findings also revealed that fiscal decentralization promoted human development and encouraged peaceful co-existence among the provinces in Pakistan. Jumadi et al (2013) carried out a study using panel data of 29 districts and 9 cities in East Java Province of Indonesia from 2007 to 2010. The aim of the study was to determine the effect of fiscal decentralization on various economic indices including human development.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Fiscal decentralization is the delegation of economic or monetary functions to the lower level governments from the government at the top (Rauf, Khan, Ali, Qureshi, Ahmad & Anwar, 2017). It is believed that economic devolution encourages accountability and transparency at all levels of government and public administration (Gogoi, 2017) and it is trusted to be a solution to all kinds of economic and political challenges facing developing countries despite its inherent glitches (Jumadi, Ghozali & Khusaini, 2013).…”
Section: Introductionmentioning
confidence: 99%